Some Limits to Arguing Virtuously - Bowell, Tracy (Informal Logic, 2021)
In this paper, I consider whether there are limits to virtuous argumentation in certain situations.  I consider three types of cases: 1) arguing against denier discourses, 2) arguing with people who make bigoted claims, and 3) cases in which marginalised people are expected to exercise virtues of argument from a position of limited agency. For each type of case, I look at where limits to arguing responsibly might be drawn. I argue that there are situations in which we might withdraw from engagement for practical reasons and others in which withdrawing or refraining from engagement is a responsible way to deal with a particular position. Finally, I argue that in the third type of case, expecting the marginalised to argue as though on even terms with the positions of the dominant risks perpetrating argumentative harm.